Best friend or spy: a qualitative meta‐synthesis on the impact of continuous glucose monitoring on life with Type 1 diabetes. Issue 4 (27th December 2017) - Messer, L. H.; Johnson, R.; Driscoll, K. A.; Jones, J.
Abstract: Aims: This is a meta‐synthesis of extant qualitative literature related to impact of continuous glucose monitoring (CGM). CGM has been available for a decade for the management of Type 1 diabetes and is the lynchpin of future artificial pancreas technologies. Clinical uptake of CGM is an important area of inquiry. The purpose of this meta‐synthesis is to understand the impact of CGM on individuals with Type 1 diabetes and others (parents, significant others, providers) in order to design appropriate clinical interventions for adherence. Methods: Studies published in English between 2007 and 2017 were included, reflecting commercial CGM availability. PubMed, PsychINFO, CINALH, Web of Science and EMBASE databases were queried using search terms related to CGM, qualitative, experience and Type 1 diabetes. Included articles contained original qualitative or mixed‐method research on CGM, sensor‐augmented pump or closed‐loop therapies. Articles underwent quality appraisal and thematic interpretive integration by a multidisciplinary team. Results: Nine articles (343 participants) met the inclusion criteria and were included in the synthesis. Six novel themes emerged: interacting with CGM, burden of living with CGM, feeling different from others, feeling empowered, interacting with glucose information and impact on relationships. Conclusion: CGM affects physical, emotional and relational aspects of life. Clinicians can help minimize the burden of CGM with carefully delivered education and expectation‐setting with individuals. Empowerment and relational partnerships in diabetes care can be explored to maximize satisfaction with CGM. Systematic interpretive synthesis of qualitative studies provides a comprehensive, contextual understanding of the impact of CGM on daily life and relationships. What's new?: Continuous glucose monitoring (CGM) is the cornerstone of future diabetes technologies, and it is essential that healthcare providers comprehend the user experience with CGM in order to promote sustained use. This qualitative meta‐synthesis synthesizes nine studies (343 participants) to provide a meaningful picture of the impact of CGM: interacting with CGM, emotional burden, feeling different, feeling empowered, using glucose information and affecting relationships. This synthesis identifies targets for intervention including optimizing CGM settings, discussing empowerment strategies, and forming partnerships with parents, significant others and providers.